Anisotropic Imprint of Amorphization and Phase Separation in Manganite Thin Films via Laser Interference Irradiation. Issue 5 (16th September 2014) - Ding, Junfeng; Lin, Zhipeng; Wu, Jianchun; Dong, Zhili; Wu, Tom
<x xml:space="preserve">Abstract</x> Materials with mesoscopic structural and electronic phase separation, either inherent from synthesis or created via external means, are known to exhibit functionalities absent in the homogeneous counterparts. One of the most notable examples is the colossal magnetoresistance discovered in mixed‐valence manganites, where the coexistence of nano‐ to micrometer‐sized phase‐separated domains dictates the magnetotransport. However, it remains challenging to pattern and process such materials into predesigned structures and devices. In this work, a direct laser interference irradiation (LII) method is employed to produce periodic stripes in thin films of a prototypical phase‐separated manganite Pr0.65(Ca0.75Sr0.25)0.35MnO3 (PCSMO). LII induces selective structural amorphization within the crystalline PCSMO matrix, forming arrays with dimensions commensurate with the laser wavelength. Furthermore, because the length scale of LII modification is compatible to that of phase separation in PCSMO, three orders of magnitude of increase in magnetoresistance and significant in‐plane transport anisotropy are observed in treated PCSMO thin films. Our results show that LII is a rapid, cost‐effective and contamination‐free technique to tailor and improve the physical properties of manganite thin films, and it is promising to be generalized to other functional materials.